A Methodology for Improving Students’ Speech Compensation in English through Web-Based Resources - Jangirova Xadicha Oybek qizi (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract: The rapid development of digital technologies has significantly influenced foreign language teaching methodologies. One of the key challenges in English language learning is students’ limited ability to compensate for linguistic gaps during oral communication. Speech compensation refers to learners’ capacity to maintain communication despite insufficient vocabulary, grammatical knowledge, or pronunciation skills by using strategies such as paraphrasing, gestures, fillers, and contextual clues. This article explores an effective methodology for improving students’ speech compensation skills in English through the use of web-based resources. The study analyzes theoretical foundations of speech compensation, identifies pedagogical advantages of web-based learning environments, and proposes a step-by-step instructional model integrating digital platforms, multimedia tools, and interactive communication tasks. The findings suggest that web-based resources enhance learners’ communicative confidence, strategic competence, and overall speaking performance by providing authentic materials, immediate feedback, and opportunities for real-life interaction.